The flight of the eagle: The charismatic leadership of Sá Carneiro in Portugal's transition to democracy - Zúquete, José Pedro (2015)
This article explores the impact of the leadership of Francisco Sá Carneiro, the first leader of the Portuguese Social Democratic Party, and Prime Minister, in the tumultuous years of Portugal's transition to democracy in the 1970s. Sá Carneiro was and still is revered as a unique charismatic figure within the party, and is viewed today as the founder of the Democratic Right in Portugal. This qualitative analysis emphasizes major aspects of Sá Carneiro's career and leadership, paying special attention to the development of charismatic dynamics between the leader and his supporters. The author argues that Sá Carneiro's discourse and actions throughout the years were a major factor in the emergence and consolidation of a charismatic community around the leader that persists to this day.